Unlocking the Potential of Polar Organometallic Reagents in Sustainable Solvents - Garcia-Álvarez, Joaquín; Capriati, Vito (SynOpen)
Polar organometallic reagents of the s-and d-block are key tools for C–C and C–heteroatom bond formation. Recent advances have shown that these highly reactive species can operate efficiently in sustainable solvents like water and Deep Eutectic Solvents, under air and at room temperature. Acting as living solvents, these media enable sustainable organometallic transformations and redefine classical reactivity paradigms through the principle of green chemistry.